Lipids production and nutrients recycling by microalgae mixotrophic culture in anaerobic digestate of sludge using wasted organics as carbon source. (February 2020) - Tan, Xiao-Bo; Yang, Li-Bin; Zhang, Wen-Wen; Zhao, Xian-Chao
Highlights: Mixotrophic culture in anaerobic digestate of sludge using wasted organics. Acidified starch wastewater addition increased lipids productivity by 3.2-fold. Mixotrophic culture improved the quality of biodiesel with higher saturation. Abstract: Insufficient organics in anaerobic digestate of sludge limited algal mixotrophic culture and caused low lipids production. In this study, enhancing lipids production and pollutants removal by adding acidified starch wastewater was tested for Chlorella pyrenoidosa mixotrophic culture. The results showed that an optimal addition of acidified starch wastewater into anaerobic digestate of sludge (1:1, v/v) improved biomass and lipids production by 0.5-fold (to 2.59 g·L −1 ) and 3.2-fold (87.3 mg·L −1 ·d −1 ), respectively. The acidified starch wastewater addition also improved the quality of algal biodiesel with higher saturation (typically in C16:0 and C18:0). In addition, 62% of total organic carbon, 99% of ammonium and 95% of orthophosphate in mixed wastewater were effectively removed by microalgae. This study provides a promising way to improve biodiesel production and nutrients recovery from anaerobic digestate of sludge using waste carbon source.